Increased discordance between HeartScore and coronary artery calcification score after introduction of the new ESC prevention guidelines. Issue 1 (March 2015) - Diederichsen, Axel C.P.; Mahabadi, Amir-Abbas; Gerke, Oke; Lehmann, Nils; Sand, Niels P.; Moebus, Susanne; Lambrechtsen, Jess; Kälsch, Hagen; Jensen, Jesper M.; Jöckel, Karl-Heinz; Mickley, Hans; Erbel, Raimund
Abstract: Objectives: The European HeartScore has traditionally differentiated between low and high-risk countries. Until 2012 Germany and Denmark were considered to be high-risk countries but have now been defined as low-risk countries. In this survey we aim to address the consequences of this downgrading. Methods: A screening of 3932 randomly selected (mean age 56 years, 46% male) individuals from Germany and Denmark free of cardiovascular disease was performed. Traditional risk factors were determined, and the HeartScore was measured using both the low-risk and the high-risk country models. A non-contrast Cardiac-CT scan was performed to detect coronary artery calcification (CAC). Results: Agreement of HeartScore risk groups with CAC groups was poor, but higher when applying the algorithm for the low-risk compared to the high-risk country model (agreement rate: 77% versus 63%, and weighted Kappa: 0.22 versus 0.15). However, the number of subjects with severe coronary calcification (CAC score ≥400) increased in the low and intermediate HeartScore risk group from 78 to 147 participants (from 2.7 % to 4.2 %, p = 0.001), when estimating the risk based on the algorithm for low-risk countries. Conclusion: As a consequence of the reclassification of Germany and Denmark as low-risk countries more people with severe atherosclerosis will be classified as having a low or intermediate risk of fatal cardiovascular disease. Highlights: The European Society of Cardiology (ESC) has changed the prevention guidelines. We examined the presence of coronary atherosclerosis and risk of cardiovascular events applying the new guidelines. Using the new ESC guidelines, more people with objective evidence of severe atherosclerosis might be misclassified. This suggest the need for further diagnostic testing in particular of individuals at intermediate risk.